Five-Year, Disease-Free Survival after Repeat Palliative Multimodality Therapy in a Patient with Recurrent Metastastic Bladder Cancer - Sebastian Fetscher; Jan Schmielau; Wolfgang Schulze-Seemann (The Scientific World Journal, 2007)
In appropriately selected cases, palliative therapeutic strategies can be adapted to those special features of cancer biographies that indicate an atypical course of disease. Elucidating these features, and adapting multimodal treatment strategies to them, can lead to significantly superior effects when compared to the routine application of conventional treatment algorhythms. A case of regionally metastactic bladder cancer is presented that documents the value of repeat debulking-surgery and repeat radiotherapy leading to unexpected short-term and long-term treatment results.